2022
DOI: 10.1002/mp.15583
|View full text |Cite
|
Sign up to set email alerts
|

In vivo assessment of hypertensive nephrosclerosis using ultrasound localization microscopy

Abstract: As a typical chronic kidney disease (CKD), hypertensive nephrosclerosis (HN) is a common syndrome of hypertension, characterized by chronic kidney microvascular damage. Early diagnosis of microvascular damage using conventional ultrasound imaging encounters challenges in sensitivity and specificity owing to the inherent diffraction limit. Ultrasound localization microscopy (ULM) has been developed to obtain microvasculature and microvascular hemodynamics within the kidney, and would be a promising tool for the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 86 publications
0
11
0
1
Order By: Relevance
“…Our results demonstrated no significant difference was showed in blood flow patterns between benign and malignant thyroid nodules as showed in Figure 3 . This diagnostic variability may be since CDFI cannot overcome the diffraction limit of ultrasound to truly reveal intra-nodular microvascular information ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results demonstrated no significant difference was showed in blood flow patterns between benign and malignant thyroid nodules as showed in Figure 3 . This diagnostic variability may be since CDFI cannot overcome the diffraction limit of ultrasound to truly reveal intra-nodular microvascular information ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the last several decades, the application of contrast-enhanced ultrasound (CEUS) on thyroid-related diseases has greatly improved. CEUS can significantly enhance the US contrast echo of the bloodstream, nevertheless, the imaging resolution of CEUS is still limited by the diffraction limit of US applied ( 14 ). Therefore, CEUS is still insufficient to observe the microvasculature at the capillary level and also the microvascular flow rate (MFR) within the micro-vessels.…”
Section: Introductionmentioning
confidence: 99%
“…Super-resolution (SR) ultrasound imaging has the potential to visualize the microvasculature in vivo, but the literature on pathological changes in the renal vasculature is limited [ 9 , 10 , 11 ]. One approach for SR imaging is based on localizing gas-filled intravascular microbubbles (MBs) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, unlike sham-operated mice, mice with unilateral ischemia-reperfusion-induced chronic kidney disease had decreased vascular density and increased tortuosity in the renal cortex [19]. In another study, a vasodilator-induced decrease in microbubble velocity was found in the cortex and the deeper-lying medulla of rat kidneys [20], and lastly, increased microbubble velocity was found in the cortical radial arteries of hypertensive rats [21]. The cortical vessels of a human kidney have also been visualized with SRUS [22].…”
mentioning
confidence: 97%
“…In einer anderen Studie wurde eine durch Vasodilatatoren induzierte Abnahme der Geschwindigkeit von Mikrobläschen im Cortex und im tiefer liegenden Mark von Rattennieren festgestellt [20]. Schließlich wurde eine erhöhte Geschwindigkeit von Mikrobläschen in der kortikalen A. radialis hypertensiver Ratten gefunden [21]. Die kortikalen Gefäße einer menschlichen Niere wurden ebenfalls mit SRUS visualisiert [22].…”
unclassified